2016
DOI: 10.3847/0004-637x/829/2/121
|View full text |Cite
|
Sign up to set email alerts
|

Probing for Evidence of Plumes on Europa With HST/Stis

Abstract: Roth et al. (2014a) reported evidence for plumes of water venting from a southern high latitude region on Europa -spectroscopic detection of off-limb line emission from the dissociation products of water. Here, we present Hubble Space Telescope (HST) direct images of Europa in the far ultraviolet (FUV) as it transited the smooth face of Jupiter, in order to measure absorption from gas or aerosols beyond the Europa limb. Out of ten observations we found three in which plume activity could be implicated. Two sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
211
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(221 citation statements)
references
References 30 publications
10
211
0
Order By: Relevance
“…Attempts to confirm the presence of plumes through the observation of plume aurora have not been successful (Roth et al 2014a(Roth et al , 2015 and earlier searches with Galileo did not reveal signs of geophysical activity (Phillips et al 2000). Recently, HST images of Europa in transit of Jupiter, taken with an FUV filter by Sparks et al (2016), revealed absorption features at the limb on three occasions in 2014 January, March and April. If the absorption is due to water vapor, the plume features require line-of-sight H 2 O column densities in the range of (0.7-3.3)×10 17 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to confirm the presence of plumes through the observation of plume aurora have not been successful (Roth et al 2014a(Roth et al , 2015 and earlier searches with Galileo did not reveal signs of geophysical activity (Phillips et al 2000). Recently, HST images of Europa in transit of Jupiter, taken with an FUV filter by Sparks et al (2016), revealed absorption features at the limb on three occasions in 2014 January, March and April. If the absorption is due to water vapor, the plume features require line-of-sight H 2 O column densities in the range of (0.7-3.3)×10 17 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…If such activity continued today, then direct study of the oceanic composition may be possible, but the question of modern geologic activity remains. Recent observations using the Hubble Space Telescope (HST) have hinted at the possibility of active water vapor plumes at Europa (Roth et al 2014a(Roth et al , 2014bSparks et al 2016Sparks et al , 2017. However, the detections have been sporadic and tenuous, making confirming the existence of plumes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…We simulate an area 156 km in radius (corresponding to our ALMA resolution in this region) centered on 276°W and 16°. 8 S, which is coincident with the Galileo thermal anomaly in the potential plume source region (Sparks et al 2016(Sparks et al , 2017. We model the case of an endogenic thermal anomaly by raising the geothermal heat flux beneath the lowest layer of our simulation (five diurnal skin depths ≈0.75 m at our best-fit parameters).…”
Section: Fits To Alma and Galileo Ppr Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavy energetic ions, which have their own precipitation patterns, remove ice in the very top layer (see below) and also preferentially eliminate smaller grains (e.g., Cassidy et al, 2013 ). In addition, the possible presence of endogenic activity, such as a plume on Europa ( Roth et al, 2014;Sparks et al, 2016 ), may create local discrepancies in the spatial distribution of grain sizes and therefore correlations with geomorphological units ( Ligier et al, 2016 ).…”
Section: Bombardment Patternsmentioning
confidence: 99%